2016
DOI: 10.1039/c6cp02134d
|View full text |Cite
|
Sign up to set email alerts
|

Optical response and gas sequestration properties of metal cluster supported graphene nanoflakes

Abstract: The possibility of obtaining metal cluster (M3O(+), M = Li, Na, K) supported pristine, B-doped and BN-doped graphene nanoflakes (GR, BGR and BNGR, respectively) has been investigated by carrying out density functional theory (DFT) based calculations. Thermochemical analysis reveals the good stability of M3O(+)@GR/BGR/BNGR moieties. The dynamic stability of M3O(+)@GR/BGR/BNGR moieties is confirmed through an atom-centered density matrix propagation simulation at 298 K up to 500 fs. Orbital and electrostatic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Larger stabilization interaction energies, E 2 , are known to cause stronger interactions between the bonds. [48][49][50][51][52] Therefore, the results suggested that Fe 2+ complexation was stronger, which was in good agreement with the reduced N/O distance between the ligand heads (from 2.825Å in uncomplexed merocyanine to 2.549Å in the Fe 2+ complex). Furthermore, the E 2 value would increase with decreasing metal center charge.…”
Section: Nbo Analysissupporting
confidence: 72%
“…Larger stabilization interaction energies, E 2 , are known to cause stronger interactions between the bonds. [48][49][50][51][52] Therefore, the results suggested that Fe 2+ complexation was stronger, which was in good agreement with the reduced N/O distance between the ligand heads (from 2.825Å in uncomplexed merocyanine to 2.549Å in the Fe 2+ complex). Furthermore, the E 2 value would increase with decreasing metal center charge.…”
Section: Nbo Analysissupporting
confidence: 72%
“…35 This means that using superalkali OM 3 as a dopant may be a better choice. Noteworthily, the β 0 values of OM 3 + @(GDY/GTY)are much larger than those of previously reported superalkali (M 3 O + , M = Li, Na, and K) supported graphene nanoflakes (GR) (8.4×10 2 -3.1×10 3 au), 64 which indicates that the largely π-conjugated graphyne is superior to graphene in producing complexes with large β 0 values.…”
Section: Figurementioning
confidence: 68%
“…Thereafter, further endeavors have been devoted to designing NLO molecules by doping superalkalis on different nanocages, including C 24 N 24 , Si 12 C 12 , C 20 , and B 40 . In addition, NLO materials can also be obtained by interacting superalkalis with other complexants, such as graphdiyne, hexamethylenetetramine, phenalenyl,– modified graphene, and P 4 molecules . Superalkalis can also be utilized as building blocks of alkalides, which was first revealed by Wu and co‐workers .…”
Section: Applications Of Superalkalismentioning
confidence: 99%